The Effect of N/O Elements on the Microstructure and Mechanical Properties of Ti-N-O Alloys - Mingqi Shi; Ruiduo Chen; Chengsong Zhang; Zhenzhao Xu; Hanke Hu; Xiaolong Zhou; Guodong Cui (Metals)
A novel Ti-N-O composite was prepared by powder nitriding/oxynitriding combined with the spark plasma sintering (SPS) method. The effects of N/O on the microstructure and mechanical properties of the Ti-N-O alloy were systematically studied. The results showed that the addition of N/O elements significantly improved the mechanical properties of commercially pure titanium (cp-Ti). The hardness reached 298.8 HV0.1 while the yield strength can reach 666 MPa. And, the O element played a leading role in regulating the microstructure and morphology of the Ti-N-O alloy. With the addition of the O element, the microstructure showed an equiaxed structure, and the characterization showed that this region is an O-enriched region, and that a small amount of nano-TiO2 particles appeared in the alloy, which together led to the change in the microstructure. At the same time, more large-angle grain boundaries were generated in the Ti-N-O alloy. This study investigated a new method for the preparation of titanium materials and provides new ideas for researching medical titanium materials.